O museu vai à escola com a arqueologia : percepções de alunos e professores - Aguiar, Liliana (2018)
"Ver, Tocar e Sentir a Maia" is an heritage mediation project developed by the Educational Services at the Museu de História e Etnologia da Terra da Maia. e study carried out focused particularly on the activity e Museum goes to school with archeology. It aimed at identifying its value, merit and usefulness to the school community, exploring perceptions and associated learning. e research plan was based on the English model for learning in museums, Inspiring Learning for All, by the Museums, Libraries and Archives. is study allowed us to recognize perceptions, motivations and project contributions to the teaching and learning at local schools.